2013
DOI: 10.1007/s10072-013-1436-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between G2385R and R1628P polymorphism of LRRK2 gene and sporadic Parkinson’s disease in a Han-Chinese population in south-eastern China

Abstract: The G2385R and R1628P polymorphisms of the leucine-rich repeat kinase 2 (LRRK2) gene have been reported to be associated with Parkinson's disease (PD), but no data are available on Han-Chinese population of south-eastern China. This study aimed to investigate whether G2385R and R1628P variants are associated with sporadic PD in this population. Total 1,060 subjects were enrolled; including 550 unrelated healthy controls and 510 patients with sporadic PD. Genotyping of polymorphisms was performed by PCR-restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Totally, 14 studies711131520212223242526272829 were included from across all the ethnic Han-Chinese population that mainly located in Mainland China, Singapore and Taiwan. Process of searching for and screening studies was showed in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Totally, 14 studies711131520212223242526272829 were included from across all the ethnic Han-Chinese population that mainly located in Mainland China, Singapore and Taiwan. Process of searching for and screening studies was showed in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…We next analysis the available studies711252628 to identify the gender whether influence the outcome of PD with R1628P in LRRK2. The association of R1628P with PD remained significant in male (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations